HIV-1 infected lymphoid organs upregulate expression and release of the cleaved form of uPAR that modulates chemotaxis and virus expression. - Manuela Nebuloni (Public Library of Science (PLoS), 2013)
Cell-associated receptor for urokinase plasminogen activator (uPAR) is released as both full-length soluble uPAR (suPAR) and cleaved (c-suPAR) form that maintain ability to bind to integrins and other receptors, thus triggering and modulating cell signaling responses. Concerning HIV-1 infection, plasma levels of suPAR have been correlated with the severity of disease, levels of immune activation and ineffective immune recovery also in individuals receiving combination anti-retroviral therapy (cART). However, it is unknown whether and which suPAR forms might contribute to HIV-1 induced pathogenesis and to the related state of immune activation. In this regard, lymphoid organs represent an import site of chronic immune activation and virus persistence even in individuals receiving cART. Lymphoid organs of HIV-1(+) individuals showed an enhanced number of follicular dendritic cells, macrophages and endothelial cells expressing the cell-associated uPAR in comparison to those of uninfected individuals. In order to investigate the potential role of suPAR forms in HIV-1 infection of secondary lymphoid organs, tonsil histocultures were established from HIV-1 seronegative individuals and infected ex vivo with CCR5- and CXCR4-dependent HIV-1 strains. The levels of suPAR and c-suPAR were significantly increased in HIV-infected tonsil histocultures supernatants in comparison to autologous uninfected histocultures. Supernatants from infected and uninfected cultures before and after immunodepletion of suPAR forms were incubated with the chronically infected promonocytic U1 cell line characterized by a state of proviral latency in unstimulated conditions. In the contest of HIV-conditioned supernatants we established that c-suPAR, but not suPAR, inhibited chemotaxis and induced virus expression in U1 cells. In conclusion, lymphoid organs are an important site of production and release of both suPAR and c-suPAR, this latter form being endowed with the capacity of inhibiting chemotaxis and inducing HIV-1 expression.